MULTIPLE ANTIBIOTIC RESISTANCE AND ESBL PRODUCING KLEBSIELLA PNEUMONIAE ISOLATED FROM CLINICAL URINE SAMPLES SAMPLES - H. RAJESHWARI; H. RAJESHWARI; AJAY OLI; R. KELMANI CHANDRAKANTH (The Bioscan, 2010)
Extended spectrum â-lactamases (ESBLs) continue to be a major problem in clinical setups world over, conferring resistance to the expanded spectrum cephalosporins. An attempt was made to study ESBL production among Klebsiella pneumoniae and to evaluate the antimicrobial resistant pattern in Klebsiella pneumoniae isolated from urine sample of the hospitalizes patients especially suffering from urinary tract infection. Antimicrobial susceptibility test revealed Ceftazidime, Cefuroxime, Ceftriaxone, Cephotaxime and Nalidixic acid showed 94% of resistance, Ampicillin 91%, Gentamicine 88% and Imipenem showed the lowest percentage of resistance (4%). Standard Double disc synergy test (SDDS) method showed 90% of the isolates were ESBL producers. Thus, in the present study, a large number of isolates were found to be MDR and ESBL producers. SDDD were found to be better method for ESBLs. Continued monitoring of drug resistance is necessary in clinical settings for proper disease management and also an alternative therapy.